Pedestrian Ring Bridge - James Carpenter (Oz, 1996)
A key seaport for over 150 years, Bremerhaven, Germany provides an important gateway to Europe and overseas. Founded in 1827 with a current population of 130,000, Bremerhaven is rapidly developing from a commercial and industrial center to a cultural and recreational maritime center.